Frontløberne som motiv: 2019-protesterne i Hongkong - Corlin Frederiksen, Mai (K&K - Kultur og Klasse, 2023)
The 2019 protests in Hong Kong unfolded with a visual forcefulness that shaped a movement that was at once popular and radical, peaceful and belligerent, orderly and sabotaging. One of the movement’s central instruments was to occupy the territory of Hong Kong with visual protest material. Protest walls spread with lightning speed from early July and from August and September, the contents of the city’s protest walls were updated every single day by independent, self-organized groupings and individuals. As long as the walls were updated with the latest information, the protest movement could prove that it was still ready for battle and that the Hong Kong they were all fighting for was right there on the wall in front of them. The image of the frontliners as the ones leading the fight against the police came to play a central role in the formation of a political identity for the protest movement. As the protest movement developed and the violent clashes with the police intensified, the images of the frontliners, dressed in black, wearing gas masks and safety goggles and with flag in their hands, emerged as the image of the protest movement. In this article, I follow the evolution of the image of the frontliners and the attempt to create a visual language that shapes this specific movement. I follow the development of the frontliners as parts of a history of protest and as parts of an ensemble of protest figures and protest-specific events. I explore what the frontliners and their images do as they unfold in the dynamic between the resistance the movement provides and the oppression they encounter.